2020
DOI: 10.1177/1060028020922542
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation Management for Impella Percutaneous Ventricular Assist Devices: An Analysis of a Single-Center Experience

Abstract: Background: Impella devices offer temporary mechanical circulatory support for cardiogenic shock. The manufacturer recommends systemic anticoagulation with a target activated clotting time of 160 to 180 s but provides no guidance on how to manage both the heparinized purge solution and the additional intravenous heparin needed to reach this therapeutic range. Previous publications demonstrated a lack of standardization in heparin management for Impella devices. Objective: The purpose of this study was to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…9,12 Bleeding events did not correlate with heparin purge solution, overall systemic heparin exposure, or anticoagulation targets when utilizing the aPTT to monitor heparin efficacy in either our study or the prior studies. 4,9 However, we did find an anti-Xa level greater than 0.4 IU/mL to be associated with a risk for bleeding, for those patients that had these values available. Although protocols for anticoagulation are in place, many centers deviate off protocol and decisions are guided by patient-specific factors.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…9,12 Bleeding events did not correlate with heparin purge solution, overall systemic heparin exposure, or anticoagulation targets when utilizing the aPTT to monitor heparin efficacy in either our study or the prior studies. 4,9 However, we did find an anti-Xa level greater than 0.4 IU/mL to be associated with a risk for bleeding, for those patients that had these values available. Although protocols for anticoagulation are in place, many centers deviate off protocol and decisions are guided by patient-specific factors.…”
Section: Discussionmentioning
confidence: 55%
“…Despite manufacturer recommendations, large variability exists with respect to selection of heparin purge concentration, use of concomitant intravenous heparin, and choice of monitoring assay, even among large volume Impella ® centers. 3,4 Bleeding is a known and common complication of anticoagulation, but limited data exists to guide decision making regarding anticoagulation strategies in these complex patients.…”
Section: Introductionmentioning
confidence: 99%
“…19 The purge solution is utilized to create a pressure barrier against the inflow of blood, preventing blood from entering the motor housing. 17 Interestingly, three of the five patients (60%) on the D5W purge solution required tPA. Though the sample size of D5W purge solution patients is low, the relative use of tPA was much higher in this patient group compared with the BIV purge solution cohort.…”
Section: Discussionmentioning
confidence: 98%
“…The time to therapeutic PTT was on average 37.7 h. For reference, a recent study comparing two UFH AC protocols during Impella use reported that median time to therapeutic range PTT was 12 h (IQR 11–19) in one cohort, and 15.5 (IQR 5–26) in another cohort. 17 Our study nomograms are displayed in Tables 5 and 6. The relatively longer time to therapeutic range PTT using BIV was explored by our pharmacy team; based on these findings a new dosing protocol was developed and implemented.…”
Section: Discussionmentioning
confidence: 99%
“…39 Finally, a recently published abstract of 30 patients under Impella support compared two different low-intensity anticoagulation regimens (goal aPTT 45-55 s or anti-Xa of 0.2-0.4 IU/ml). 40 The aPTT group was associated with higher heparin dosing requirements, increased time to goal range, shorter time in goal range, and more bleeding episodes.…”
Section: Intr Avenous Anti Coag Ul Ati Onmentioning
confidence: 90%